Slow and steady: Sustained effects of lexico-semantic associations can mediate referential impairments in schizophrenia - Ditman, Tali (2011)
The present study investigated the contribution of lexico-semantic associations to impairments in establishing reference in schizophrenia. We examined event-related potentials as schizophrenia patients and healthy demographically-matched controls read five-sentence scenarios. Sentence 4 introduced a noun which referred back to three possible referents introduced in sentences 1–3. These referents were contextually appropriate, contextually inappropriate but lexico-semantically associated, and contextually inappropriate and lexico-semantically non-associated. In order to determine whether participants had correctly linked the anaphor to its referents, the final sentence reintroduced each referent and participants indicated whether the last two sentences referred to the same entity. Results indicated that between 300–400msec, patients, like healthy controls, used discourse context to link the noun with its preceding referent. However, between 400–500msec, neural activity in patients was modulated only by lexico-semantic associations rather than discourse context. Moreover, patients were also more likely than controls to incorrectly link the noun with contextually-inappropriate, but lexico-semantically associated, referents. Results suggest that at least some types of referential impairments may be driven by sustained activation of contextually inappropriate lexico-semantic associations.